Manejo de plantaciones comerciales de café (Coffe arábica) a través de implementación de diseños agroforestales con especies frutales en zona premontana - Galarza Salvatierra, Jairo Tito (2022)
In Ecuador it is important to manage commercial plantations in agroforestry systems, because they help in the production of desired products from the harvest of the established crop and at the same time, they can expand the harvest of these trees designated to be worth as wood, firewood, charcoal and take advantage of their fruits. Coffee growing in Ecuador is an activity with a notorious economic, social and ecological importance. Coffee in this country generates work for its diverse field work, at the moment of implementing an agroforestry system we improve the conditions of the climate and at the same time the texture of the soil, contributing organic matter in a natural way and thus being able to maintain the soil more fertile for the associated cultivation, and to be able to generate greater production with all the types of species planted. In our country there are very diverse zones between flora and fauna such as the premontane forests, which is an area full of life where human activity created by man can develop, such as the cultivation of coffee that has a good adaptability in humid and dry zones where it maintains a long life of successful production, The coffee capacity can be conserved without any inconvenience until the development of the timber trees and fruit species is completed. A thinning could be carried out in order to generate an economic aid and provide more sunlight to the associated crop to stimulate the development of the flowers and fruits of the coffee plant.